PENGARUH INTERNET FINANCIAL REPORTING, TINGKAT PENGUNGKAPAN INFORMASI BERBASIS WEBSITE, DAN JUMLAH SAHAM BEREDAR TERHADAP FREKUENSI PERDAGANGAN SAHAM - Erna Sulistyowati; Meidy Tiara Nur Sausan; Faluthia Fitri Puspaningrum (BAJ: Behavioral Accounting Journal, 2021)
The aims of this study are: to prove, test, empirically and analyze the impact of Internet Financial Reporting on Stock Trading Frequency, the impact of the Level of Information Website Disclosure on Stock Trading Frequency, and the impact of the Number of Outstanding Shares on the Trading Frequency of Shares. This study uses quantitative methods using secondary data taken from the company's website and the IDX in 2016-2018. In this study, data analysis techniques uses with multiple linear regression SmartPLS 3.29. The results of this study were conducted if (1) Internet Financial Reporting has no effect on Stock Trading Frequency, (2) Website-Based Information Disclosure Level has no influence on Stock Trading Frequency, (3) Number of Outstanding Shares will have no effect. The implication of this research is that it pays attention to financial information in the company that is entered through the website then investors can predict future financial performance and prospects and can make decisions related to investment decision making, by uploading and updating information owned by the company can provide education to the public. users and prosper the company. The high and low use of information information sites will have a small impact on the magnitude of the company's impact on investor decisions. In addition, taking into account factors other than the number of shares outstanding, such as fundamental factors and stock prices, can attract investors to invest in the company, because basically investors in buying shares must choose liquid shares.